2015
DOI: 10.1371/journal.pone.0119596
|View full text |Cite
|
Sign up to set email alerts
|

Improved Assessment of Orbital Stability of Rhythmic Motion with Noise

Abstract: Mathematical techniques have provided tools to quantify the stability of rhythmic movements of humans and machines as well as mathematical models. One archetypal example is the use of Floquet multipliers: assuming periodic motion to be a limit-cycle of a nonlinear oscillator, local stability has been assessed by evaluating the rate of convergence to the limit-cycle. However, the accuracy of the assessment in experiments is questionable: Floquet multipliers provide a measure of orbital stability for determinist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…For example, it has been shown that Floquet analysis of a simple nonlinear walking model with stochastic noise over-estimates orbital stability. 43,44 In addition, human walking is not exactly periodic, 45 and it has even been suggested that it might not be a stable limit cycle. 46…”
Section: B Poincaré Maps and Floquet Multipliersmentioning
confidence: 99%
“…For example, it has been shown that Floquet analysis of a simple nonlinear walking model with stochastic noise over-estimates orbital stability. 43,44 In addition, human walking is not exactly periodic, 45 and it has even been suggested that it might not be a stable limit cycle. 46…”
Section: B Poincaré Maps and Floquet Multipliersmentioning
confidence: 99%
“…Another non-intuitive effect of noise on estimation was highlighted in a recent study on Floquet multipliers, a method for assessing orbital stability of rhythmic movements. Noise induces a bias in the estimation of orbital stability [ 57 ]. Another example for the surprising effect of noise is the two-thirds power law that is widely observed in human movements [ 58 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of biomechanical engineering, orbital stability is defined using estimated Floquet multipliers from measured data of physical rotation and orbital movement [11][12][13]. The study by [11] provided a method that generated accurate estimates with noisy experimental data. However, there is no generalized method to choose the proper Poincaré section.…”
Section: Introductionmentioning
confidence: 99%